A statistical study of convective and dynamic instabilities in the polar upper mesosphere above Tromsø - Satonori Nozawa; Norihito Saito; Takuya Kawahara; Satoshi Wada; Takuo T. Tsuda; Sakiho Maeda; Toru Takahashi; Hitoshi Fujiwara; Viswanathan Lakshmi Narayanan; Tetsuya Kawabata; Magnar G. Johnsen (Earth, Planets and Space, 2023)
Abstract We have studied the convective (or static) and dynamic instabilities between 80 and 100 km above Tromsø (69.6° N, 19.2° E) using temperature and wind data of 6 min and 1 km resolutions primarily almost over a solar cycle obtained with the sodium lidar at Tromsø. First, we have calculated Brunt–Väisälä frequency (N) for 339 nights obtained from October 2010 to December 2019, and the Richardson number (Ri) for 210 nights obtained between October 2012 to December 2019. Second, using those values (N and Ri), we have calculated probabilities of the convective instability (N 2 < 0) and the dynamic instability (0 ≤ Ri < 0.25) that can be used for proxies for evaluating the atmospheric stability. The probability of the convective instability varies from about 1% to 24% with a mean value of 9%, and that of the dynamic instability varies from 4 to 20% with a mean value of 10%. Third, we have compared these probabilities with the F10.7 index and local K-index. The probability of the convective instability shows a dependence (its correlation coefficient of 0.45) of the geomagnetic activity (local K-index) between 94 and 100 km, suggesting an auroral influence on the atmospheric stability. The probability of the dynamic instability shows a solar cycle dependence (its correlation coefficient being 0.54). The probability of the dynamic instability shows the dependence of the 12 h wave amplitude (meridional and zonal wind components) (C.C. = 0.52). The averaged potential energy of gravity waves shows decrease with height between 81 and 89 km, suggesting that dissipation of gravity waves plays an important role (at least partly) in causing the convective instability below 89 km. The probability of the convective instability at Tromsø appears to be higher than that at middle/low latitudes, while the probability of the dynamic instability is similar to that at middle/low latitudes. Graphical Abstract